Research on the Healing Potential of Rural Community Streets From the Perspective of Audiovisual Integration: A Case Study of Four Rural Communities in China - Fu, Erkang; Ren, Yuxin; Li, Xi; Zhang, Lei (Frontiers in Public Health, 2022)
Rural communities have become a hot topic in academic circles because of their graceful natural environment and great healing potential. However, existing research still lacks attention to the street space in rural communities and rarely considers its integrated visual and soundscape design in terms of their effect on public health. As a result, the healing potential of rural community streets cannot be fully used in design practice. Relevant audiovisual materials were collected from a field investigation in four rural communities in southwestern China. Based on these data, the subjective and objective healing index data of subjects under comprehensive audiovisual conditions were collected and analyzed through laboratory experiments. The results revealed that type of street space affects healing potential, and the artificial–natural enclosed and natural semi-enclosed streets are the street types with the best healing effect. When the total sound pressure level was 55dB(A), the sound combination with birdsong accounting for 70% had a significant positive effect on improving the healing effect of rural community streets. In contrast, the sound combination with birdsong accounting for 50% or less had no significant effect on improving healing. The subjective healing perception of street space in rural communities was significantly positively correlated with aesthetic preferences. There was also a significant correlation between subjective healing perception and physiological index data in the audiovisual combination. This research explored the impact of different types of street space and sound combinations on the healing effect of rural community streets in an integrated audiovisual environment and provided a scientific basis for the healing landscape design of rural community streets in an integrated audiovisual environment. It was expected to provide new ideas for the construction of rural community landscapes, including acoustic landscapes, to promote physical and mental healing.